DOES A GOOD CENTRAL BANKER MAKE A DIFFERENCE?. (26th February 2016) - Neuenkirch, Matthias; Tillmann, Peter
Abstract : The personalities of central bankers moved center stage during the recent financial crisis. Indeed, several central bankers even became "superstars." In this article, we investigate whether superstar central bankers have an impact on economic performance. We employ school grades given to central bankers by the financial press, defining as superstars those central bankers receiving the top grade. First, we explain the grades in a probit estimation with measures of economic performance, institutional features, and personal characteristics. Second, we employ a matching approach to account for the endogeneity of grading with respect to economic performance. Using entropy balancing, we identify credible counterfactuals for top‐graded central bankers, that is, nonsuperstar central bankers who face similar situations. Comparing the economic performance of both groups, we find that superstars do indeed matter: a top‐graded central banker faces a significantly more favorable output‐inflation tradeoff than his peers. This effect is driven by outstanding central bankers in both advanced and emerging economies and is especially prevalent in the precrisis subsample. ( JEL E52, E58)